MAQASHID SYARIAH DALAM MANAGEMENT PENYELENGGARAAN IBADAH HAJI - Aye Sudarto; Mesta Wahyu Nita; Kukuh Cahyono (Institut Agama Islam Negeri Metro, 2023)
Hajj management aims to provide the best possible guidance, service and protection through a good management system and management so that the pilgrimage can run safely, orderly, smoothly and comfortably in accordance with Islamic teachings. Pilgrims to be able to carry out their worship independently until they get a mabrur hajj. The system for organizing the pilgrimage is continuously undergoing changes and improvements. The increasing number of citizens to perform the pilgrimage needs to improve the quality of organizing the pilgrimage that is comfortable, orderly and in accordance with sharia provisions, so that sharia goals can be achieved. The paradigm in this paper is critical spiritualist with the perspective of maqashid sharia. Paradigma is the basic assumption regarding the subject matter, purpose and nature of the study material being studied. The applied research paradigm is a literature study with a qualitative approach. At the managerial level, the implementation of the pilgrimage is included in maqashid daruriyah (primary). Because its existence is sufficient to determine the continuity of the implementation of the pilgrimage. Because if it is not implemented and organized properly it will result in chaos and even result in the non-implementation of the pilgrimage.